A Dangerous Balance: Indiscriminate Counterterrorism Measures and Mobilization against the State. Issue 4 (2nd June 2021) - Mathieson, Nicola
Abstract: This paper explores the unintended consequences of counterterrorism measures by reconceptualizing them as forms of state repression. In line with the study of state repression, this paper distinguishes between two types of counterterrorism measures—selective and indiscriminate. Therefore, I argue the impacts of both forms of counterterrorism measures mirror those of selective and indiscriminate state repression. This paper is particularly concerned with the relationship between indiscriminate counterterrorism measures and consequent mobilization against the state. Drawing on cases of indiscriminate counterterrorism measures in Northern Ireland and Bosnia and Herzegovina, this paper argues that indiscriminate counterterrorism measures, like indiscriminate state repression, exacerbate divisions between the state and its citizens, increasing the risk of the violence that counterterrorism measures are assumed to prevent. Résumé: Cet article explore les conséquences involontaires des mesures antiterroristes en les reconceptualisant en tant que formes de répression étatique. S'alignant sur l'étude de la répression étatique, cet article distingue deux types de mesures antiterroristes: les mesures sélectives et les mesures indiscriminées. Je soutiens donc que l'impact de ces deux formes de mesures antiterroristes reflète celui des deux formes de répression étatique: la répression sélective et la répression indiscriminée. Cet article s'intéresse particulièrement à la relation entre les mesures antiterroristes indiscriminées et la mobilisation contre l'État qui en résulte. Il s'appuie sur des cas de mesures antiterroristes indiscriminées qui ont été employées en Irlande du Nord et en Bosnie-Herzégovine et soutient que les mesures antiterroristes indiscriminées, tout comme la répression étatique indiscriminée, exacerbent les divisions entre l'État et ses citoyens, accroissant ainsi le risque de violence que les mesures antiterroristes sont supposées empêcher. Resumen: En este artículo, se exploran las consecuencias imprevistas de las medidas antiterroristas al reconceptualizarlas como formas de represión estatal. En línea con el estudio de la represión estatal, en este documento se distinguen entre dos tipos de medidas antiterroristas: selectivas e indiscriminadas. Por lo tanto, sostengo que el impacto de ambas formas de medidas antiterroristas refleja el de la represión estatal selectiva e indiscriminada. En este documento, se aborda especialmente la relación entre las medidas antiterroristas indiscriminadas y la consiguiente movilización contra el Estado. En función de los casos de medidas antiterroristas indiscriminadas en Irlanda del Norte y Bosnia y Herzegovina, en este documento se argumenta que las medidas antiterroristas indiscriminadas, al igual que la represión estatal indiscriminada, exacerban las divisiones entre el Estado y sus ciudadanos, y potencian el riesgo de casos de violencia que se supone que las medidas antiterroristas deben evitar.